Bridges, String Art, and Bézier Curves - Gross, Renan (The Best Writing on Mathematics 2013, 2014)
The Jerusalem Chords Bridge, in Israel, was built to make way for the city’s light rail train system. However, its design took into consideration more than just utility—it is a work of art, designed as a monument. Its beauty rests not only in the visual appearance of its criss-cross cables, but also in the mathematics that lies behind it. Let us take a deeper look into these chords. The Jerusalem Chords Bridge is a suspension bridge, which means that its entire weight is held from above. In this case, the deck is connected to a single tower by powerful